EFFECT OF MULTI - ENZYME ON PRODUCTION PERFORMANCE AND CARCASS TRAITS OF NANDANAM BROILER - 2 CHICKENS - K. Sangilimadan,; A.V.Omprakash,; K.Premavalli,; C.Pandian,; R.Richard Churchill, (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted  at Institute of Poultry Production and Management (IPPM), Madhavaram Milk colony, Chennai-51.Three hundred and sixty (360) day-old straight run Nandanam broiler - 2 chicks were individually weighed, wing banded and randomly assigned to three different dietary treatments with two replicates  and reared on deep litter system for a period of 8 weeks. The results showed that supplementation of muti-enzyme at the rate of 500g per ton of feed (T2) in Nandanam broiler-2 ration were significantly higher (P